2019
DOI: 10.1017/s2045796018000793
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of DSM-5 mental disorders in a nationally representative sample of children in Taiwan: methodology and main findings

Abstract: Aims There has been a lack of prevalence estimates of DSM-5 mental disorders in child populations at the national level worldwide. This study estimated the lifetime and 6-month prevalence of mental disorders according to the DSM-5 diagnostic criteria in Taiwanese children. Methods Taiwan's National Epidemiological Study of Child Mental Disorders used the stratified cluster sampling to select 69 schools in Taiwan resulting in a nationally representative sample of 4816 children in grades 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 40 publications
(87 reference statements)
4
86
3
1
Order By: Relevance
“…Attention-deficit/hyperactivity disorder (ADHD) is a prevalent neurodevelopmental disorder with a lifetime prevalence of 10.1% according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) diagnostic criteria [1] in a nationally representative sample of children in Taiwan [2]. Although neurocognitive etiologies contribute to ADHD symptom development [1], ADHD symptoms are often attributed to affected children's unwillingness in self-control or intentional opposition and misunderstanding of ADHD increases both social rejection and hostile emotions in peers, teachers, family members, and neighbors [3].…”
Section: Stigma To Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
“…Attention-deficit/hyperactivity disorder (ADHD) is a prevalent neurodevelopmental disorder with a lifetime prevalence of 10.1% according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) diagnostic criteria [1] in a nationally representative sample of children in Taiwan [2]. Although neurocognitive etiologies contribute to ADHD symptom development [1], ADHD symptoms are often attributed to affected children's unwillingness in self-control or intentional opposition and misunderstanding of ADHD increases both social rejection and hostile emotions in peers, teachers, family members, and neighbors [3].…”
Section: Stigma To Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
“…The current study is part of Taiwan's National Epidemiological Study of Child Mental Disorders, a nationally representative school-based survey of child mental disorders commissioned by Taiwan's Ministry of Health and Welfare from June 1, 2015, to January 31, 2017 [Y. L. Chen, Chen, Lin, Shen, & Gau, 2019;Y. L. Chen, Shen, & Gau, 2017].…”
Section: Study Samplementioning
confidence: 99%
“…L. Chen, Shen, & Gau, 2017]. The detailed study methodology can be accessed in other papers [Y. L. Chen, Chen, Lin, et al, 2019;Y. L. Chen, Shen, et al, 2017;.…”
Section: Study Samplementioning
confidence: 99%
“…However, the lack of increase in the recognition of EDs at a younger age concerns us because the age at assessment is a significant predictor of mortality for patients with AN (Arcelus, Mitchell, Wales, & Nielsen, 2011). A recently published study reported that the lifetime prevalence of AN in a nationally representative sample of 8-14-year-old Taiwanese youths was 0.2% (Chen, Chen, Lin, Shen, & Gau, 2019), which is a similar figure to the 0.3% in a representative sample of 13-18-year-old US adolescents (Swanson, Crow, Le Grange, Swendsen, & Merikangas, 2011). Some studies have shown that the prevalence of mental disorders overall among children and adolescents in Taiwan is comparable with that in Western countries (Chen et al, 2019;Gau, Chong, Chen, & Cheng, 2005); however, the prevalence of healthcare-detected cases that have a specific disorder (e.g., attention-deficit hyperactivity disorder) is much lower than the prevalence of community cases (Chien, Lin, Chou, & Chou, 2011).…”
Section: Discussionmentioning
confidence: 99%